( 615 ) الدورة التدريبية طويلة الأجل لموظفى وزارة الادارة المحلية: اقتصاديات الزراعة Long-term training course for Ministry of Local Administration staff: Agricultural Economics - عز الدين همام أحمد (معهد التخطيط القومى, 2026)
ملخص تناقش هذه الدراسة الأهمية الاستراتيجية للقطاع الزراعى في اقتصاد الجمهورية العربية المتحدة، موضحةً أن الزراعة تمثل حجر الزاوية في النشاط الاقتصادي ومصدرًا رئيسيًا للدخل القومي والتشغيل وتوفير الغذاء والمواد الخام اللازمة للصناعة. وتستهدف المذكرة، التي أُعدت ضمن البرنامج التدريبي طويل الأجل لموظفي وزارة الإدارة المحلية، تقديم عرض مبسط وشامل للمفاهيم الأساسية في الاقتصاد الزراعي وعلاقته بالتنمية الاقتصادية والاجتماعية. وتتناول الدراسة الخصائص المميزة للإنتاج الزراعي، وما يرتبط به من عوامل طبيعية وفنية واقتصادية تؤثر في حجم الإنتاج وكفاءته، مع تحليل لأنواع المحاصيل الزراعية وأهميتها النسبية، وتوزيع المساحات المزروعة، ومستويات الإنتاجية ومتوسطات الغلة. كما تستعرض المذكرة دور الموارد الزراعية المختلفة، وعلى رأسها الأرض والمياه والعمل ورأس المال، في تكوين الناتج الزراعي، وتوضح كيفية تأثير السياسات الاقتصادية والتسويقية على قرارات المنتجين الزراعيين. وتهتم الدراسة كذلك بتحليل مساهمة الزراعة في التجارة الخارجية من خلال الصادرات الزراعية، ودورها في توفير النقد الأجنبي ودعم ميزان المدفوعات، إضافة إلى علاقتها بعمليات التصنيع والتنمية الريفية. كما تناقش المشكلات التي تواجه القطاع الزراعي، مثل محدودية الأراضي الصالحة للزراعة، والزيادة السكانية، وتقلبات الإنتاج والأسعار، والحاجة إلى رفع الكفاءة الإنتاجية من خلال استخدام التكنولوجيا الحديثة وتحسين أساليب الإدارة الزراعية. وتؤكد الدراسة أن التنمية الزراعية لا تمثل هدفًا قطاعيًا فحسب، بل تُعد ركيزة أساسية لتحقيق التنمية الاقتصادية الشاملة، نظرًا لما تؤديه من دور في توفير الغذاء، وتحسين مستويات المعيشة، وزيادة الدخل القومي، ودعم الاستقرار الاقتصادي والاجتماعي. وتخلص إلى أن التخطيط السليم للقطاع الزراعي، والاستغلال الأمثل للموارد المتاحة، وتطوير نظم الإنتاج والتسويق الزراعي، تمثل جميعها عناصر ضرورية لتحقيق النمو الاقتصادي المستدام ورفع كفاءة الاقتصاد الوطني. This study examines the strategic importance of the agricultural sector within the economy of the United Arab Republic, emphasizing its role as a cornerstone of economic activity and a primary source of national income, employment, food supply, and industrial raw materials. Prepared as part of a long-term training program for employees of the Ministry of Local Administration, the memorandum provides a comprehensive yet accessible introduction to the principles of agricultural economics and its relationship to economic and social development. The study analyzes the distinctive characteristics of agricultural production and the natural, technical, and economic factors influencing productivity and efficiency. It reviews major crop categories, cultivated areas, production levels, and yield indicators, highlighting their contribution to the national economy. Furthermore, the memorandum discusses the roles of key agricultural resources—including land, water, labor, and capital—in determining agricultural output and examines how economic and marketing policies influence farmers’ production decisions. The study also explores agriculture’s contribution to foreign trade through agricultural exports and its significance in generating foreign exchange earnings, strengthening the balance of payments, and supporting industrial development and rural transformation. In addition, it identifies major challenges facing the agricultural sector, including limited arable land, rapid population growth, fluctuations in production and prices, and the need to enhance productivity through technological progress and improved farm management practices. The analysis underscores that agricultural development is not merely a sectoral objective but a fundamental prerequisite for comprehensive economic development, given its contribution to food security, income generation, employment creation, and social stability. The study concludes that effective agricultural planning, optimal resource utilization, modernization of production systems, and improved agricultural marketing mechanisms are essential requirements for achieving sustainable economic growth and enhancing the overall performance of the national economy.